Persepsi Posisi dan Durasi Duduk dengan Keluhan Nyeri Punggung Bawah pada Pengemudi Ojek Online - Fajriatin Eka Y. Putri; Muhammad Isman Jusuf; Dewi Suryaningsi Hiola (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the relationship between perceived sitting position and sitting duration and complaints of low back pain among Maxim online motorcycle taxi drivers in Gorontalo City. This study employed a quantitative analytical method with a cross-sectional approach. The results showed a significant relationship between perceived sitting position and complaints of low back pain (p-value = 0.000), and a significant relationship between perceived sitting duration and complaints of low back pain (p-value = 0.000). In conclusion, perceived sitting position and sitting duration are factors associated with complaints of low back pain among online motorcycle taxi drivers. Therefore, implementing ergonomic sitting positions and adjusting sitting duration is necessary to prevent low back pain.   Keywords: Sitting Duration, Lower Back Pain, Online Motorcycle Taxi Drivers, Sitting Position